(untitled) (Economic and Political Thought, 2016)
The main aim of the article is to present the Neo-Weberian State in the context of changes in the perception of the role of a state in the economy due to the global economic crisis that started at the turn of 2007. As a result of the collapse of the mortgage market in the United States, which eventually led to the collapse of many economies in the world, some experts began to see the need to increase the role of a state, weakened as a result of popularization of new solutions typical of the trend of New Public Management and New Public Governance. One proposal that has gained importance is the concept of the Neo-Weberian State proposed by C. Pollitt and G. Bouckaert. Their solution combines the best aspects of these two models with the classical Weberian bureaucracy assuming the central coordinating role of the state in countering global challenges. In the article, the author presents some of the causes of the outbreak of the global economic crisis, referring to the J.M. Keynes’ concept of ‘animal spirits’, which G. Akerlof and R. Schiller analysed based on the current problems of global economies. Next, the author assesses to what extent the Neo-Weberian State is a response to the presence of ‘animal spirits’ in the economy and shows example solutions in harmony with the proposal of C. Pollitt and G. Bouckaert in the United States and the European Union.